CYP Gene Expression and In Vivo Biological Effects of Khat Ethanol Extract, Cathinone and Cathine in Caenorhabditis elegans - Sharoen Yu Ming Lim; Mohammed Abdullah Alshawsh; Mustafa Alshagga; Cin Kong; Chee-Mun Fang; Yan Pan (Progress in Microbes and Molecular Biology)
The significant influence of khat, cathinone, and cathine on appetite suppression, reproduction impairment, and inhibitory effects on CYPs enzyme activity is widely recognised, but much remains unknown about its mode of action. This study demonstrated that exposure to high doses of KEE, cathinone, cathine and sibutramine at 12.5, 1.8, 1.8 and 1.8 mg/ml showed the most visible reduction in pharyngeal pumping rate, respectively. C. elegans showed an anomalous dynamic of reproduction rate upon exposure to these compounds but overall, showed a reduced amount of progeny. KEE, cathinone, and cathine extended the lifespan of C. elegans as compared to sibutramine and control with survival rate increments of 59.5%, 43.3%, and 15%, respectively. Quantitative RT-PCR results were insignificant, but cyp-14A3, cyp-34A9, and cyp-35A2 across all treatments were upregulated, ranging from >1 to 3-fold as compared to control. cyp genes expression could be upregulated to enhance the metabolism of khat extract, cathinone, cathine, and sibutramine in C. elegans.